Public Private Partnership Model in Tourism Development in North Toraja District - Muhammad Hidayat Djabbari; Alwi; Suryadi (Enrichment : Journal of Management, 2021)
The concept of Public Private Partnership (PPP) has proven to be more efficient and effective in public services in the tourism sector, and benefits from regional revenue (PAD), and can help the government to deal with limited resources in tourism development. This study aims to determine how the model and the success of the Public Private Partnership (PPP) in tourism development in North Toraja Regency. This research uses a qualitative approach. Data collection was carried out through interviews, observation and documentation study. Data processing and analysis techniques are carried out at three stages, namely: data reduction, presentation and drawing conclusions. The informants in this study were as follows: (a) the Department of Culture and Tourism of North Toraja Regency; (b) Owner / Manager of Ke'te Kesu ' and Lempe Negeri Above the Clouds Tourism Object; (c) Visitors / Community. The results showed: (1) Equity shows a cooperation sharing agreement that has an impact on the receipt of fees and tourism services; (2) Effectiveness, government-private cooperation runs effectively to attract revenue (retribution) and provide services to visitors or tourists; (3) Efficiencies, public-private cooperation shows that the use of resources in the development of tourist objects is proven to be more efficient by implementing public-private cooperation; (4) Exportability shows the government gets a high risk of demand to meet the needs of tourist objects and compensation to communities affected by the construction of tourist attraction facilities and infrastructure. The life cycle contract (LCC) model in the cooperation agreement (MOU) between the private sector and the government shows that it is the private sector that initiates development in tourist destinations. The private sector becomes the owner of a tourist attraction that carries out development starting from design, build, finance, and maintenance at an early stage before any cooperation with the government.